Perbandingan Nilai Hematokrit Metode Mikrohematokrit dan Metode Automatik Hematology Analyzer Zybio Z3 Menggunakan Darah Vena di Klinik Utama Restu Ibu Jepara - Asmawati, Dwi; Hartinah, Dewi; Saputro, Arief Adi (Jaringan Laboratorium Medis, 2025)
Pregnant women are one of the populations at risk of contracting Sexually Transmitted Infections (STIs) such as HIV, Syphilis, and Hepatitis B. The prevalence of HIV/AIDS transmission from mother to child is 20-50% where 5-10% occurs during pregnancy. Syphilis transmission is 69-80% and Hepatitis B transmission is more than 90% with the potential for transmission during pregnancy and childbirth being very high. Based on the Regulation of the Minister of Health of the Republic of Indonesia, regulation No. 52 of 2017 concerning the Elimination Program for Transmission of Human Immunodeficiency Virus, Syphilis, and Hepatitis B from Mother to Child or often called "Triple Elimination" aims to stop transmission from mother to child with laboratory examinations on pregnant women at least once during pregnancy. The purpose of this study was to determine the relationship between knowledge and behavior of healthy reproductive age pregnant women in the first trimester at the Lebdosari Health Center. In general, this research method is qualitative with an analytical observational approach and cross-sectional design, namely researchers come and analyze the problem directly. Data collection is carried out at once within a certain time. The population  is pregnant women in the first trimester at the Lebdosari Health Center, with a sample size of 49 people selected based on the Purposive Sampling technique. Data analysis was carried out descriptively and then continued with a bivariate test with the Kendal Tau test because the data was not normally distributed. The results of the study showed that the results of the bivariate test with the Kendal Tau test showed that there was no relationship between knowledge and behavior because the significance value p = 0.888> 0.05 with a positive correlation coefficient value (0.19) which means that there is a positive relationship between knowledge and behavior even though the relationship is weak because the value is less than 1, so that if knowledge increases, behavior will be better. It is recommended that pregnant women are advised to always maintain personal hygiene and implement a clean and healthy lifestyle to prevent infectious diseases.